Assessing the Impact of Digital Technologies on Operational Efficiency in Oil and Gas Industry: Evidence from Emerging Economies - Tarakhtiyeva , Gulmira (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The oil and gas industry is undergoing a profound digital transformation driven by the integration of advanced technologies such as the Internet of Things (IoT), artificial intelligence (AI), big data analytics, and industrial automation systems. This study evaluates the impact of these technologies on operational efficiency, focusing particularly on emerging economies. Drawing on empirical evidence and industry data, the research demonstrates that digital technologies significantly improve productivity, reduce operational costs, and enhance decision-making processes. The findings highlight that while developed economies lead in technological adoption, emerging economies exhibit rapid gains in efficiency when digital solutions are effectively implemented.